Understanding Afghan healthcare providers: a qualitative study of the culture of care in a Kabul maternity hospital. (14th November 2014) - Arnold, R; van Teijlingen, E; Ryan, K; Holloway, I
<x xml:space="preserve">Abstract</x> Objective To analyse the culture of a Kabul maternity hospital to understand the perspectives of healthcare providers on their roles, experiences, values and motivations and the impact of these determinants on the care of perinatal women and their babies. Design Qualitative ethnographic study. Setting A maternity hospital, Afghanistan. Population Doctors, midwives and care assistants. Methods Six weeks of observation followed by 22 semi‐structured interviews and four informal group discussions with staff, two focus group discussions with women and 41 background interviews with Afghan and non‐Afghan medical and cultural experts. Main outcome measures The culture of care in an Afghan maternity hospital. Results A large workload, high proportion of complicated cases and poor staff organisation affected the quality of care. Cultural values, social and family pressures influenced the motivation and priorities of healthcare providers. Nepotism and cronyism created inequality in clinical training and support and undermined the authority of management to improve standards of care. Staff without powerful connections were vulnerable in a punitive inequitable environment—fearing humiliation, blame and the loss of employment. Conclusions Suboptimal care put the lives of women and babies at risk and was, in part, the result of conflicting priorities. The underlying motivation of staff appeared to be the socio‐economic survival of their own families. The hospital culture closely mirrored the culture and core values of Afghan society. In setting priorities for women's health post‐2015 Millennium Development Goals, understanding the context‐specific pressures on staff is key to more effective programme interventions and sustainability.